1993
DOI: 10.1111/j.1600-0714.1993.tb01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of inflammatory cytokines and vascular adhesion receptors in radicular cysts

Abstract: Odontogenic cysts are one of the commonest bone destroying lesions of the maxillofacial skeleton, with the inflammatory radicular cyst being the commonest jaw cyst. Explants of radicular cysts produce an interleukin-1-like activity which could explain the osteolysis seen with these tumours though the cellular source of this osteolytic activity is unknown. In the present study, cytokines with known inflammatory and osteolytic activity: interleukin-1 (IL-1), tumour necrosis factor (TNF), interleukin-6 (IL-6), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 13 publications
3
54
1
2
Order By: Relevance
“…Bando et al showed that cytokines and growth factors released by inflammatory cells present in connective tissue can stimulate epithelial proliferation in RC and more intense inflammation may cause greater proliferative activity (16).While we did not find any statistical association in staining pattern among studied groups, it's noticeable that in one case of radicular cyst cyclin D1 expression was also seen in all layers of epithelial part. Therefore, according to Bando et al results,cyclin D1 expression in all layers may be related to the intensity of inflammation in cyst wall.…”
Section: Discussioncontrasting
confidence: 50%
“…Bando et al showed that cytokines and growth factors released by inflammatory cells present in connective tissue can stimulate epithelial proliferation in RC and more intense inflammation may cause greater proliferative activity (16).While we did not find any statistical association in staining pattern among studied groups, it's noticeable that in one case of radicular cyst cyclin D1 expression was also seen in all layers of epithelial part. Therefore, according to Bando et al results,cyclin D1 expression in all layers may be related to the intensity of inflammation in cyst wall.…”
Section: Discussioncontrasting
confidence: 50%
“…19,20 These cytokines provide activation signals to lymphocytes, 21 and in turn, the lymphocyte-derived cytokines interleukin 2 (IL-2), interleukin 6 (IL-6) and gamma interferon (IFN-g) may influence osteoclastic activity and bone remodeling. 22 Studies using an in vitro osteoclast model have suggested that the response to PMMA may directly contribute to the process of bone resorption. 23 UHMWPE wear has been significantly correlated with frequency and size of osteolytic lesions 24 and may also act to inhibit biosynthetic pathways of bone and mesenchymal tissue.…”
Section: Pathogenesis Of Aseptic Looseningmentioning
confidence: 99%
“…Other studies by evaluation of P53, P63, Ki-67, COX-2, IPO-38 and PCNA immunostaining in odontogenic cysts "to compare their proliferative activity" have also shown the higher expression of mentioned markers in parabasal layer of OKCs in contrast to DCs, RCs or normal mucosa seen in basal layer (18,19,20,21,22,23,24,25).…”
mentioning
confidence: 99%
“…Bando et al showed that cytokines and growth factors released by infl ammatory cells present in connective tissue can stimulate epithelial proliferation in RC and more intense infl ammation may cause greater proliferative activity (19). Th erefore, cyclin D1 expression in all layers may be related to the intensity of infl ammation in cyst wall.…”
mentioning
confidence: 99%